2018
DOI: 10.1016/j.vaccine.2018.02.102
|View full text |Cite
|
Sign up to set email alerts
|

“I wouldn’t really believe statistics” – Challenges with influenza vaccine acceptance among healthcare workers in Singapore

Abstract: Our findings highlight a combination of misperceptions about influenza vaccination and cognitive biases at the individual level, and challenges at the institutional level limiting uptake. Findings indicate an urgent need to provide targeted education and communication. Rather than providing more data, we recommend a widely-disseminated, locally-compiled synthesis addressing specific concerns of hesitant HCWs. Tailoring interventions to specific vocational groups should be considered. Institutional norms and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 50 publications
7
54
1
Order By: Relevance
“…Perceptions of good health status and personal immunity as reasons for an individual's influenza infection were prevalent among participants. These misperceptions are consonant with Sundaram et al's [27] findings that healthcare workers perceived influenza "as a routine illness causing temporary inconvenience but no lasting harm" (p. 1999) and with those of some healthcare workers (as found by [44,45]). This consensus indicates that more communication about the non-relationship between immunity and influenza infection is needed to redress the misperceptions among older adults in Singapore.…”
Section: Perceptions About the Influenza Diseasesupporting
confidence: 74%
See 1 more Smart Citation
“…Perceptions of good health status and personal immunity as reasons for an individual's influenza infection were prevalent among participants. These misperceptions are consonant with Sundaram et al's [27] findings that healthcare workers perceived influenza "as a routine illness causing temporary inconvenience but no lasting harm" (p. 1999) and with those of some healthcare workers (as found by [44,45]). This consensus indicates that more communication about the non-relationship between immunity and influenza infection is needed to redress the misperceptions among older adults in Singapore.…”
Section: Perceptions About the Influenza Diseasesupporting
confidence: 74%
“…This study builds on recent investigations by Sundaram and colleagues [27] that noted challenges for influenza vaccine uptake among healthcare workers in Singapore. Our study furthers this foundational work by exploring the influenza disease and vaccination misperceptions of the most vulnerable population to the disease (older adults) with the hope that such information can contribute to improved disease prevention and treatment.…”
Section: Introductionmentioning
confidence: 81%
“…It is recommended that these educational programs are supplemented by cues from healthcare workers to encourage patients to have the influenza vaccine, given the high regard participants accorded to advice from healthcare workers. Not only are interventions needed for patients, but additional training of healthcare workers may be valuable as a recent study in Singapore identified how local healthcare workers did not trust the evidence for influenza vaccination and doubted its relevance to the local context [28]. A widely-disseminated, locally-compiled synthesis addressing specific concerns of hesitant healthcare workers was recommended.…”
Section: Implications For Health Promotion Initiatives and Clinical Pmentioning
confidence: 99%
“…There are a variety of antimicrobial interventions that have been introduced to combat lung infections. For viruses this includes both preventative vaccines and in some cases antivirals (88)(89)(90)(91)(92). There are also a number of antibiotics that target bacterial pathogens and pathobionts that cause infection of the lower respiratory tract.…”
Section: Host Disease Tolerance To Infectious Diseasementioning
confidence: 99%